Shaping identity, shaping power: the politics of Kadazandusun ethnic identity in Sabah / Tony Paridi Bagang, Arnold Puyok and Neilson Ilan Mersat - Bagang, Tony Paridi; Puyok, Arnold; Mersat, Neilson Ilan (Faculty of Administrative Science and Policy Studies, 2025)
The Kadazandusun ethnic identity in Sabah, Malaysia, has long been a subject of political and sociocultural debate, particularly regarding its inclusivity and representation of Dusunic, Murutic, and Paitanic-speaking communities. Since the introduction of "Kadazandusun" as a unifying identity in 1989, efforts to consolidate this identity have been marked by contention and negotiation. Political leaders and ethnic organizations have repeatedly called for unity, transcending political ideologies, to establish a singular generic identity for the Kadazandusun that could also replace the "Lain-lain" (Others) category in official government classifications. This article examines the evolution of Kadazandusun identity politics, focusing on how political elites and ethnic organizations construct, reconstruct, and mobilize ethnic identity to achieve both cultural and political objectives. Adopting a multifaceted methodological approach—including thematic analysis, content analysis, and ethnographic methods—the study reveals that Kadazandusun ethnic identity is not static but continuously shaped by the strategic actions of political elites and the instrumentalization of identity for political and electoral gains. By analyzing these dynamics, the article provides critical insights into the complex interplay between identity construction, political leadership, and cultural representation within the Kadazandusun community.